Description of five deep caries management methods and their use in contemporary dentistry - Jodłowska, Anna; Leś-Smolarczyk, Alicja; Postek-Stefańska, Lidia (Journal of Stomatology, 2018)
Deep caries treatment is associated with the loss of hard dental tissue and pain during debridement of the cavity and is very time-consuming. Traditional management (complete caries removal) is associated with high complication rates. In order to reduce the number of problems, other methods can be used such as stepwise excavation, partial caries removal and cavity restoration during the same visit, and no dentinal caries removal. The aim of this paper is to compare the efficacy of five deep caries treatment methods based on the literature. It describes complete caries removal, indirect pulp treatment, stepwise excavation, 1-visit partial caries removal and no dentinal caries removal. The work focuses on methods which are minimally invasive in relation to hard dental tissues and ensure maximum protection of vital dental tissue. The present study suggests the need to limit complete cavity preparation in the treatment of deep caries, especially at the developmental age. Such an approach decreases the risk of pulp exposure and substantial loss of hard dental tissue to improve the conditions of secondary dentin formation.